Gestión administrativa en el Comercial Oruliaceros de la ciudad de Babahoyo periodo 2023. - Rodríguez Palma, Andy Arom (2024)
This case study was conducted in the city of Babahoyo, focusing on the Administrative Management of Comercial Oruliaceros in Babahoyo during the year 2023. It is based on a thorough analysis of the administrative practices implemented by the company. The aim is to identify the factors that impact the performance of administrative management in Comercial Oruliaceros, taking into account the various problems that arose in the different functions and areas of the company, which resulted in inefficiencies in its control system. As a result, management indicators were established to facilitate the measurement and evaluation of administrative performance. For the correct execution of the case study, the research line “Financial, Administrative, Tax, Audit, Control” was considered, which is related to the subline “Public and Private Companies and Institutions”. This allows determining a direct interaction between customers, collaborators, and the company. In addition, this work is articulated through the project of linking with society called “Young Entrepreneurs for the Encounter”, based on the idea that knowledge and practice are fundamental for emerging businesses and ventures. This analytical work concludes with the fulfillment of the objective of the study, which allowed to analyze the administrative management processes of Comercial Oruliaceros in Babahoyo during the year 2023. Therefore, the execution has been very satisfactory, considering that through the application of surveys as a research tool, the presence of organizational deficiencies that were found in the company was identified and corroborated.